What to do With Eurocentric Curricula: An Example From ‘Antigone in Ferguson’ - Chang, David (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
In their study of curriculum, teacher candidates often witness the pitfalls of Eurocentric curricula. This critical awareness of hidden biases is vital in a pluralistic society that is only now recognizing its colonial history. Indigenous communities are making bold strides in decolonizing their schools. Their notable efforts instantiate many forms of resistance to Eurocentrism in education. At the same time, there are examples in which marginalized groups seize the cultural goods of a dominant culture and assert their voice through the words of a canonized text. In this essay, I reflect on a modern interpretation of Sophocles’ Antigone and consider its relevance to curriculum studies.